FEATURES OF INTUITIVE PERCEPTION: FROM CHRISTIANITY TO POSITIVISM - Alieva, G.F (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
The article is devoted to one of the most controversial problems of science and philosophy - the problem of intuition. This problem is complex and multifaceted, and its epistemological aspect is considered here. Despite the fact that there is a certain scientific idea of intuition, the problem of whether intuition is subconscious or superconscious is not yet scientifically defined. The results of the search for sources of knowledge of the Absolute Truth by great philosophers, ranging from antiquity to modern, are compared by the author with various historically established concepts. Proceeding from the principle of Unity and continuity of Idea, the author substantiates the idea that the only way to preserve both their own West and East specifics and overcome the crisis is to form a correct attitude to the sources of the essence of the Idea. The problem of turning to the invisible part of things, and not to their manifestation, as to truth, is the central problem of ontology in the history of philosophy. The essence of this idea remains unchanged, regardless of the fact that it differs in different worldviews, depending on their forms, styles, language and religion. The article successively examines approaches to the problem of intuition at various stages of the development of social thought.